Characterizing fiber reinforced concrete incorporating zeolite and metakaolin as natural pozzolans. (December 2021) - Dabbaghi, Farshad; Sadeghi-Nik, Aref; Libre, Nicolas Ali; Nasrollahpour, Sepideh
Abstract: Supplementary cementitious materials (SCMs), including industrial by-products or natural pozzolans are widely used as a partial replacement of ordinary Portland cement (OPC) in eco-friendly concrete, to reduce the carbon footprint and enhance mechanical and durability properties. Although many experiments have been conducted to study the effect of SCMs in concrete, the research on the effect of natural pozzolans on fiber reinforced concrete (FRC) is limited. This study investigates the effect of different amounts of metakaolin and zeolite pozzolans on the mechanical properties and durability of concrete containing polypropylene fibers. A total of 99 specimens were made in 11 experimental groups and the parameters of compressive strength, tensile strength, water absorption, porosity and density of concrete specimens were evaluated. In addition, concrete specimens were tested for ultrasonic pulse velocity (UPV) and atomic force microscopy (AFM) to further study the effect of natural pozzolans on the microstructure of concrete. The performance of FRC with natural pozzolans was compared to that of reference concrete and fiber reinforced concrete without SCMs. The results indicated that the polypropylene (PP) fibers were more effective in enhancing mechanical properties of concrete in the zeolite mixtures, so that the compressive strength and tensile strength compared to reference concrete increased by 44 and 22%, respectively, while the water absorption and porosity decreased by 48 and 45%, respectively. This is attributed to the higher viscosity of the zeolite-mixtures that allowed for a better dispersion of fibers in the mixture as well as the improved bond strength between fibers and paste due to the high pozzolanic activity of zeolite. The AFM analysis, UPV, density, and permeable voids test results revealed that the FRC mixtures incorporating natural zeolite had the most dense microstructure and the least porosity and defects among all examined FRC mixtures even compared to the mixtures that incorporated metakaolin with the same cement replacement level.